DJBreezy
  • DJBreezy
Name the y value of the solution to the system of equations. Use substitution: -4x + y = 6 -5x - y = 21
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
Jamierox4ev3r
  • Jamierox4ev3r
you might have to set the two to equal each other -4x+y=6 +4x +4x --------- y=4x+6 then -5x-y=21 +5x +5x --------- -y=5x+21 y=-5x-21
Jamierox4ev3r
  • Jamierox4ev3r
then you could do this: -5x-21=4x+6 since each end equals y. Then solve for x. Once you solve for x, plug the x value into one of the equations and solve for y ^^
DJBreezy
  • DJBreezy
x=−3

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Jamierox4ev3r
  • Jamierox4ev3r
@DJBreezy does this make sense so far?
Jamierox4ev3r
  • Jamierox4ev3r
-5x-21=4x+6 +5x +5x ---------- -21=9x+6 -6 -6 --------- -27=9x /9 /9 ------ x=-3 \(\color{green}\checkmark\) that's right :)
Jamierox4ev3r
  • Jamierox4ev3r
now we solve for y -4(-3)+y=6 12+y=6 -12 -12 ------- y=-6
Jamierox4ev3r
  • Jamierox4ev3r
you can also check with the other equation -5(-3)-y=21 15-y=21 -15 -15 ------- -y=6 y=-6
Jamierox4ev3r
  • Jamierox4ev3r
both equations yield y=-6 therefore, the value of y is -6. Do you understand?
DJBreezy
  • DJBreezy
so the answer is -6??
DJBreezy
  • DJBreezy
yes and thx
Jamierox4ev3r
  • Jamierox4ev3r
no problem :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.